Numerical modeling the process of deep slab dehydration and magmatism - Hao Wu; Jiacheng Lei; Zeyu Jia; Jian Sheng; Yinan Zhu; Jian Wang (Scientific Reports)
Abstract This study uses a 2D high-resolution thermo-mechanical coupled model to investigate the dynamic processes of deep plate hydration, dehydration, and subsequent magmatic activity in ocean-continent subduction zones. We reveal the pathways and temporal evolution of water transport to the deep mantle during the subduction process. Plate dehydration plays a critical role in triggering partial melting of the deep mantle and related magmatic activity. Our study shows significant differences in the volumes of melt produced at different depths, with dehydration reactions in deeper regions being weaker compared to shallower ones. It takes a longer time to reach the suitable P-T conditions for hydrous melting in the deep mantle. The results highlight the geophysical significance of water transport in deep subduction zones and its role in magmatic processes, particularly in the formation of magma chambers beneath continental plates.